THE IMPACT OF MIGRANT WORKER INCLUSION ON PSYCHOLOGICAL WELL-BEING, WORK STRESS, AND PSYCHOLOGICAL ADAPTATION: - Mulyadi, Dadi; Rustandi, Tata; Suadma, Udin (Universitas Nusa Cendana, 2025)
This study analyzes the impact of inclusion on psychological well-being, work stress, psychological adaptation, and competitiveness among Indonesian migrant workers in Taiwan. Using 170 respondents from the informal sector (caregivers), SEM-PLS is applied to examine variable relationships. Results show that inclusion significantly affects psychological well-being, work stress, psychological adaptation, and competitiveness. Psychological well-being enhances competitiveness, while work stress has no significant impact. Psychological adaptation plays a crucial role in increasing competitiveness. Mediation analysis reveals that psychological well-being and psychological adaptation significantly mediate the relationship between inclusion and competitiveness, whereas work stress does not. The study concludes that inclusion improves well-being, adaptation, and competitiveness, despite increasing work stress, which does not influence competitiveness. An inclusive work environment is essential to support the well-being and competitiveness of migrant workers by reducing stress and fostering psychological adaptation. Keywords : Competitiveness; Migrant Worker Inclusion; Psychological Well-being; Work Stress; Psychological Adaptation